RESEARCH ON GPS HEIGHT FITTING BASED ON LINEAR REGRESSION MODEL - K. Y. Yang; K. Y. Yang; L. L. Liu; L. L. Liu; L. K. Huang; L. K. Huang; L. K. Huang; L. K. Huang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
This paper mainly expounds the parameter estimation method, the outlier diagnosis and the establishment of the optimal regression equation in the linear regression model theory, the analysis of the principle of the polynomial fitting model, the derivation of the algorithm process, and the research on the accuracy evaluation method.The GPS survey area is fitted and calculated. The fitting model is analyzed and compared in detail. The better parameter values and regression equation models of the planar region are estimated. The fitting accuracy meets the requirements of the fourth level measurement, which can be used in actual engineering. Replace the fourth level measurement in the application.